2018
DOI: 10.1002/ange.201801537
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Directed Dimerization of Bowl‐Shaped Radical Anions to Form a σ‐Bonded Dibenzocorannulene Dimer

Abstract: Designed site-directed dimerization of the monoanion radicals of a p-bowl in the solid state is reported. Dibenzo[a,g]corannulene (C 28 H 14 )w as selected based on the asymmetry of the charge/spin localization in the C 28 H 14 C À anion. Controlled one-electron reduction of C 28 H 14 with Cs metal in diglyme resulted in crystallization of an ew dimer, [{Cs + (diglyme)} 2 (C 28 H 14 ÀC 28 H 14 ) 2À ]( 1), as revealed by single crystal X-rayd iffraction study performed in ab road range of temperatures.T he C À … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The formation of radical ions after charge transfer can significantly relax chemical bonds. This relaxation is beneficial to the breakage of chemical bonds and can lead to the swelling of the coal. Pruitt and Xue reported that the bond energy is significantly reduced after the formation of free radical cations or anions through charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of radical ions after charge transfer can significantly relax chemical bonds. This relaxation is beneficial to the breakage of chemical bonds and can lead to the swelling of the coal. Pruitt and Xue reported that the bond energy is significantly reduced after the formation of free radical cations or anions through charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the dimerization reaction of two bowlshaped PAH monoanion radicals was first reported in 2018 by the Petrukhina and Rogachev groups. 33 Recently, Han and coworkers 34 have synthesized a series of stable radicals derived from an N-heterocyclic carbene by enhancing the spin delocalization. Petrukhina and co-workers found that introducing one electron to triphenylene produces a radical anion with antiaromaticity that can be stabilized by attractive electrostatic interactions and loss of antiaromaticity through charge transfer to the metal cation.…”
Section: Introductionmentioning
confidence: 99%